Mechanisms of action of bisphosphonates: similarities and differences and their potential influence on clinical efficacy. - Russell, R; Watts, N; Ebetino, F; Rogers, M (2008)
UNLABELLED: Bisphosphonates (BPs) are well established as the leading drugs for the treatment of osteoporosis. There is new knowledge about how they work. The differences that exist among individual BPs in terms of mineral binding and biochemical actions may explain differences in their clinical behavior and effectiveness. INTRODUCTION: The classical pharmacological effects of bisphosphonates (BPs) appear to be the result of two key properties: their affinity for bone mineral and their inhibitory effects on osteoclasts. DISCUSSION: There is new information about both properties. Mineral binding affinities differ among the clinically used BPs and may influence their differential distribution within bone, their biological potency, and their duration of action. The antiresorptive effects of the nitrogen-containing BPs (including alendronate, risedronate, ibandronate, and zoledronate) appear to result from their inhibition of the enzyme farnesyl pyrophosphate synthase (FPPS) in osteoclasts. FPPS is a key enzyme in the mevalonate pathway, which generates isoprenoid lipids utilized for the post-translational modification of small GTP-binding proteins that are essential for osteoclast function. Effects on other cellular targets, such as osteocytes, may also be important. BPs share several common properties as a drug class. However, as with other families of drugs, there are obvious chemical, biochemical, and pharmacological differences among the individual BPs. Each BP has a unique profile that may help to explain potential clinical differences among them, in terms of their speed and duration of action, and effects on fracture reduction.